2016
DOI: 10.1128/jb.00906-15
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Acinetobacter: from the Cell Surface to Infinity and Beyond

Abstract: The genus Acinetobacter encompasses multiple nosocomial opportunistic pathogens that are of increasing worldwide relevance because of their ability to survive exposure to various antimicrobial and sterilization agents. Among these, Acinetobacter baumannii, Acinetobacter nosocomialis, and Acinetobacter pittii are the most frequently isolated in hospitals around the world. Despite the growing incidence of multidrug-resistant Acinetobacter spp., little is known about the factors that contribute to pathogenesis. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 120 publications
2
89
0
Order By: Relevance
“…Capsule and its negative surface charge may well be the primary virulence function of the pathogen, as it is the primary defense the bacteria have against complement-mediated destruction and opsonization, as well as phagocytic uptake (74,(104)(105)(106)(107). Hypervirulent strains have been reported that resist innate immune uptake, which may have unusual or mutated capsular phenotypes (70,105,(108)(109)(110).…”
Section: Acinetobacter Virulence Factorsmentioning
confidence: 99%
“…Capsule and its negative surface charge may well be the primary virulence function of the pathogen, as it is the primary defense the bacteria have against complement-mediated destruction and opsonization, as well as phagocytic uptake (74,(104)(105)(106)(107). Hypervirulent strains have been reported that resist innate immune uptake, which may have unusual or mutated capsular phenotypes (70,105,(108)(109)(110).…”
Section: Acinetobacter Virulence Factorsmentioning
confidence: 99%
“…(1)(2)(3)(4). Bacteremia is caused by toxic shock in 25% to 30% of the cases and usually occurs due to disseminated intravascular coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…NFGNB are bacteria that are generally considered opportunistic pathogens selected by repeated and prolonged antibiotic treatments (Ferroni et al, 2003). Acinetobacter baumannii is resistant to several antibiotics (Howard et al, 2012, Weber et al, 2015, and its epidemic distribution is due to its manual transmission and survival in the hospital environment (Lahsoune et al, 2007;Ducel et al, 2002). The level of Acinetobacter baumannii identified in NFGNB in our study is higher than the 28.57% reported by Liazid (2016) for Tlemcen hospital in Algeria.…”
Section: Distribution Of Distribution Of Nfgnbmentioning
confidence: 99%